Crystallographic and spectroscopic assignment of the proton transfer pathway in [FeFe]-hydrogenases. Issue 1 (December 2018) - Duan, Jifu; Senger, Moritz; Esselborn, Julian; Engelbrecht, Vera; Wittkamp, Florian; Apfel, Ulf-Peter; Hofmann, Eckhard; Stripp, Sven; Happe, Thomas; Winkler, Martin
Abstract The unmatched catalytic turnover rates of [FeFe]-hydrogenases require an exceptionally efficient proton-transfer (PT) pathway to shuttle protons as substrates or products between bulk water and catalytic center. For clostridial [FeFe]-hydrogenase CpI such a pathway has been proposed and analyzed, but mainly on a theoretical basis. Here, eleven enzyme variants of two different [FeFe]-hydrogenases (CpI and HydA1) with substitutions in the presumptive PT-pathway are examined kinetically, spectroscopically, and crystallographically to provide solid experimental proof for its role in hydrogen-turnover. Targeting key residues of the PT-pathway by site directed mutagenesis significantly alters the pH-activity profile of these variants and in presence of H2 their cofactor is trapped in an intermediate state indicative of precluded proton-transfer. Furthermore, crystal structures coherently explain the individual levels of residual activity, demonstrating e.g. how trapped H2 O molecules rescue the interrupted PT-pathway. These features provide conclusive evidence that the targeted positions are indeed vital for catalytic proton-transfer. [FeFe]-hydrogenases catalyze H2 -evolution and -oxidation at very high turnover-rates. Here the authors provide experimental evidence for the proposed proton-transfer (PT) pathway by kinetically, spectroscopically, and crystallographically characterizing eleven mutants from the two [FeFe]-hydrogenases CpI and HydA1.